Characteristics of infants exposed to maternal tuberculosis and chemoprophylaxis using three months of isoniazid and rifampicin - Mathivha, Khakhu Tshilidzi (My University, 2016)
Background: Though features of infants with congenital tubercuiosis (TB) are known including being low-birth-weight (LBw), features of in-utero TB-exposed infants including non-infected are not well reported. Infants bom to TB-infected women are at risk of contracting TB post-delivery, therefore chemoprophylaxis is recommended, and this includes use of isoniazid and rifampicin combination, but littie is known about its effectiveness. Objective: To determine features of in-utero TB-exposed infants and proportion with TB after chemoprophylaxis with isoniazid and rifampicin. Methods: Retrospective review of records of TB-infected women and their infants, from ZA07-20rc. Clinical features of mothers and infants at time of delivery; and follow-up of infants after completion of isoniazid and rifampicin are described. Results: Eighty-eight infants bom to 86 women with a diagnosis of TB were studied. TB diagnosis was made peripartum in24.4Yoof women, 23.3%had exka-pulmonary TB. Among those diagnosed antepa$um 46.2o/owere on treatment for >2 months. Human immunodeficiency virus (HIV) was positive in 97.7Yo;wi& CD4 count <200 cells/mm3 in 74'6yo' Eight mothers (9.3%) died before discharge. There were 56 {63.6%)LBW and 45 (51'2W preterun infants. Culture for acid-fast-bacilli was positive in 4 (4.5%)infants. At 3- months follow-up, 17 (20.2%)defaulted, and among 67 who returned, 7 OAoA)did not return for Mantoux test reading, 1160 (1.7%)had positive Manroux. Conclusion: Majority of TB-exposed infants are born to mothers with TB/ HIV co-infection. A high proportion of TB-exposed infants are born preterm and LBW. The high attrition rate made it difficult to assess effectiveness of chemoprophylaxis with isoniazid and rifampicin
A dissertation submitted to the Faculty of Health Sciences, university of the witwatersrand, in fulfilment ofthe requirements for the degree of Master of Medicine (paediatrics) Johannesburg, 20 I 6
Keywords: Chemoprevention; Infant; Isoniazid; Rifampin; Tuberculosis